The endovascular repair of blunt traumatic thoracic aortic injury in Asia: A systematic review and meta-analysis. (April 2019) - Ho, Xin Nee; Wee, Ian JY; Syn, Nicholas; Harrison, Michael; Wilson, Lauren; Choong, Andrew MTL
Introduction: Blunt traumatic thoracic aortic injury, the second leading cause of death from trauma, poses unique challenges in its management. However, there has not yet been a corresponding consolidated series of outcomes reported in Asia, which this systematic review aims to address. Method: This review was performed as per the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Searches were performed on MEDLINE, EMBASE, Google Scholar, and Cochrane Database for studies performed in Asia reporting the endovascular management of blunt traumatic thoracic aortic injury. Risk of bias was assessed using the Newcastle-Ottawa scale. Meta-analyses of pooled proportions were performed using the metaprop command in STATA. This review has been prospectively registered in PROSPERO (CRD42018083773). Results: Sixteen retrospective cohort studies were included, reporting a total of 238 patients. The pooled Injury Severity Score was 32.5 (95%CI 27.8–37.1). The pooled mean time to operation from diagnosis was 39.2 hours (95%CI 24.6–53.8 hours), and operation time was 100 min (95%CI 63.5–136.5 min). The pooled rate of procedural conversion from endovascular repair to open surgery was 0.17% (95%CI 0–3.7%), and the proportion of left subclavian artery coverage was 55% (95%CI 37–72%). The pooled prevalence of intra-operative all-cause and aortic-related mortality was 0.72% (95%CI 0–4.9%) and 0.27% (95%CI 0–3.8%), respectively. The pooled prevalence of 30-day all-cause and aortic-related mortality was 2.2% (95%CI 0.16–5.6%) and 2.1% (95%CI 0–3.7%), respectively. In terms of 30-day complication, the pooled prevalence rates of type 1 endoleak, endograft complications, vascular access injury, strokes, and aortic re-rupture were 1.2%, 0.34%, 0.14%, 0.02%, and 0.01%, respectively. There were no cases of types II and III endoleak, and renal failure. Conclusion: Short- to mid-term results for thoracic endovascular aortic repair for blunt traumatic thoracic aortic injury in Asia are encouraging. However, there is a distinct disparity in reporting across Asia. We propose a prospective database for outcome reporting post thoracic endovascular aortic repair in this patient population, and ongoing follow up to assess long-term efficacy of this treatment strategy.